Responses of the kelp Saccharina latissima (Phaeophyceae) to the warming Arctic: from physiology to transcriptomics. Issue 1 (7th August 2019) - Li, Huiru; Monteiro, Cátia; Heinrich, Sandra; Bartsch, Inka; Valentin, Klaus; Harms, Lars; Glöckner, Gernot; Corre, Erwan; Bischof, Kai
Abstract : The Arctic region is currently facing substantial environmental changes due to global warming. Melting glaciers cause reduced salinity environments in coastal Arctic habitats, which may be stressful for kelp beds. To investigate the responses of the kelp Saccharina latissima to the warming Arctic, we studied the transcriptomic changes of S. latissima from Kongsfjorden (Svalbard, Norway) over a 24‐hour exposure to two salinities (Absolute Salinity [SA ] 20 and 30) after a 7‐day pre‐acclimation at three temperatures (0, 8 and 15°C). In addition, corresponding physiological data were assessed during an 11‐days salinity/temperature experiment. Growth and maximal quantum yield for photosystem II fluorescence were positively affected by increased temperature during acclimation, whereas hyposalinity caused negative effects at the last day of treatment. In contrast, hyposalinity induced marked changes on the transcriptomic level. Compared to the control (8°C – SA 30), the 8°C – SA 20 exhibited the highest number of differentially expressed genes (DEGs), followed by the 0°C – SA 20. Comparisons indicate that S. latissima tends to convert its energy from primary metabolism (e.g. photosynthesis) to antioxidant activity under hyposaline stress. The increase in physiological performance at 15°C shows that S. latissima in the Arctic region can adjust and might even benefit from increased temperatures. However, in Arctic fjord environments its performance might become impaired by decreased salinity as a result of ice melting.